Disinfection with sodium hypochlorite in hospital environmental surfaces in the reduction of contamination and infection prevention: a systematic review - Samantha Storer Pesani Pereira; Hadelândia Milon de Oliveira; Ruth Natalia Teresa Turrini; Rúbia Aparecida Lacerda (SciELO, 2015)
OBJECTIVETo search for evidence of the efficiency of sodium hypochlorite on environmental surfaces in reducing contamination and prevention of healthcare-associated infection HAIs.METHODSystematic review in accordance with the Cochrane Collaboration.RESULTSWe analyzed 14 studies, all controlled trials, published between 1989-2013. Most studies resulted in inhibition of microorganism growth. Some decreased infection, microorganism resistance and colonization, loss of efficiency in the presence of dirty and surface-dried viruses.CONCLUSIONThe hypochlorite is an effective disinfectant, however, the issue of the direct relation with the reduction of HAIs remains. The absence of control for confounding variables in the analyzed studies made the meta-analysis performance inadequate. The evaluation of internal validity using CONSORT and TREND was not possible because its contents were not appropriate to laboratory and microbiological studies. As a result, there is an urgent need for developing specific protocol for evaluating such studies.